Hippocampal apoptosis, neurogenesis suppression, BDNF, TrkB, CREB expression in depressed female and male rats - Golgeli, A.; Ozdiraz, K. Yazgan; Degirmencioglu, S.; Yapislar, H.; Yay, A. H.; Bakkaloglu, U. (ELSEVIER, 2019)
32nd Congress of the European-College-of-Neuropsychopharmacology (ECNP), Copenhagen, DENMARK, SEP 07-10, 2019